2015
DOI: 10.1007/s40520-015-0479-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vestibular rehabilitation in the elderly: a systematic review

Abstract: Clinical trials indicate that vestibular rehabilitation represents an effective means of treating elderly patients with vestibular disorders; however, evidence of its effectiveness remains lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 31 publications
1
17
0
8
Order By: Relevance
“…In comparison with the effectiveness of vestibular rehabilitation in other medical conditions with a deterioration of the vestibular system similar to multiple sclerosis, our results are in accordance with those of a previous review in the elderly [34]. As in the current study, this previous research reported that after a vestibular rehabilitation programme (the Cawthorne-Cooksey protocol was the most commonly employed intervention protocol), dizziness improved in the experimental group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In comparison with the effectiveness of vestibular rehabilitation in other medical conditions with a deterioration of the vestibular system similar to multiple sclerosis, our results are in accordance with those of a previous review in the elderly [34]. As in the current study, this previous research reported that after a vestibular rehabilitation programme (the Cawthorne-Cooksey protocol was the most commonly employed intervention protocol), dizziness improved in the experimental group.…”
Section: Discussionsupporting
confidence: 92%
“…As in the current study, this previous research reported that after a vestibular rehabilitation programme (the Cawthorne-Cooksey protocol was the most commonly employed intervention protocol), dizziness improved in the experimental group. In the elderly population, a progressive loss of nerve cells in the peripheral and central vestibular system, inducing dizziness and vertigo, occurs in a similar way to the occurrence in multiple sclerosis [34].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In another study conducted by Badke et al on the effect of vestibular rehabilitation and balance exercises on adults of age, more than 65 having central or peripheral vestibular dysfunction was seen and found that both types of patients improved on DGI score indicating the effectiveness of vestibular rehabilitation in these patients 31 . Diandra Caroline Martins e Silva et al in their systemic review conducted in 2015 concluded that vestibular rehabilitation has shown efficacy in the treatment of elderly patients who suffer from vestibular disorders 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the rehabilitation of postural balance, different methods can be found in the current literature analyzing the effects of those interventions in different groups of the population. In that way, vestibular rehabilitation [14], vibration [15], and multimodal exercise show benefits on balance in the elderly. Innovative methods such as virtual reality [16], complementary therapies such as mind-body movements [17], treadmill training [18], and peripheral somatosensory stimulation [19] have been shown to have different benefits on balance after stroke.…”
Section: Instructionmentioning
confidence: 96%